2013
DOI: 10.1111/mmi.12478
|View full text |Cite
|
Sign up to set email alerts
|

An Alba‐domain protein contributes to the stage‐regulated stability of amastin transcripts in Leishmania

Abstract: SummaryLeishmania infantum promastigotes differentiate into amastigote forms within the phagolysosome of mammalian macrophages causing visceral leishmaniasis. Delta-amastins belong to a multigenic surface protein family of potential virulence factors that are specifically expressed in the amastigote life cycle stage through distinct regulatory elements in the 3′ UTR controlling either mRNA stability or translation. Here, we provide novel insights on trans-acting factors regulating amastin developmental gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 66 publications
(95 reference statements)
1
49
0
Order By: Relevance
“…Also, DRBD13 has been demonstrated to negatively regulate mRNAs encoding for cell membrane-associated proteins via interaction with AREs of the target transcripts (Jha et al 2015). More recently, we showed that the Leishmania infantum Alba3 protein can stabilize the developmentally regulated amastin transcripts specifically in the amastigote stage upon binding to a U-rich element in the 3 ′ UTR (Dupé et al 2014).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Also, DRBD13 has been demonstrated to negatively regulate mRNAs encoding for cell membrane-associated proteins via interaction with AREs of the target transcripts (Jha et al 2015). More recently, we showed that the Leishmania infantum Alba3 protein can stabilize the developmentally regulated amastin transcripts specifically in the amastigote stage upon binding to a U-rich element in the 3 ′ UTR (Dupé et al 2014).…”
Section: Introductionmentioning
confidence: 83%
“…Regulation of mRNA decay rates through interactions of RNA-binding proteins (RBPs) with cis-acting sequences in 3 ′ UTRs of trypanosomatid transcripts is central in determining the fate of mRNAs and thus fine-tuning developmental gene expression (McNicoll et al 2005;Bringaud et al 2007;Haile and Papadopoulou 2007;Haile et al 2008;Müller et al 2010b;Kramer 2012;Clayton 2013). Several RBPs, such as zinc finger proteins, Alba-domain proteins, and Pumilio (PUF) proteins, have been found to regulate mRNA stability in trypanosomatids (Clayton 2013;Dupé et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To isolate AMA(LD) parasites in vivo, 1x10 7 serum-treated META L.mexicana cells were injected in rumps of [8][9][10][11][12] week old Balb/c mice (Charles River, UK). After 4 months the mice were sacrificed and the lesions harvested as described [6,24].…”
Section: Mice Infectionsmentioning
confidence: 99%
“…For parasite lifecycle progression, both metacyclogenesis (procyclic to metacyclic promastigote) and amastigogenesis (metacyclic promastigote to amastigote) differentiation processes require tightly coordinated gene regulation [2]. To date, many ciselements but strikingly few trans-regulators have been implicated in Leishmania developmental progression [3][4][5][6][7][8][9][10][11]. The identification of Leishmania trans-regulators that bind mRNAs in a stage-specific manner lends vital insight into the cellular processes which promote and enable parasite survival.…”
Section: Introductionmentioning
confidence: 99%
“…Cis -acting motifs within 3'UTRs of Leishmania transcripts have been shown to play major roles in regulating mRNA stability and translation [815]. We have previously identified and characterized a large class of cis -acting elements in Leishmania , SIDERs for S hort I nterspersed DE generate R etroposons [11].…”
Section: Introductionmentioning
confidence: 99%